Mutation Analysis of Mycobacterial rpoB Genes and Rifampin Resistance Using Recombinant Mycobacterium smegmatis - Nakata, Noboru (American Society for Microbiology, 2012)
Rifampin is a major drug used to treat leprosy and tuberculosis. The rifampin resistance of Mycobacterium leprae and Mycobacterium tuberculosis results from a mutation in the rpoB gene, encoding the β subunit of RNA polymerase. A method for the molecular determination of rifampin resistance in these two mycobacteria would be clinically valuable, but the relationship between the mutations and susceptibility to rifampin must be clarified before its use. Analyses of mutations responsible for rifampin resistance using clinical isolates present some limitations. Each clinical isolate has its own genetic variations in some loci other than rpoB, which might affect rifampin susceptibility. For this study, we constructed recombinant strains of Mycobacterium smegmatis carrying the M. leprae or M. tuberculosis rpoB gene with or without mutation and disrupted their own rpoB genes on the chromosome. The rifampin and rifabutin susceptibilities of the recombinant bacteria were measured to examine the influence of the mutations. The results confirmed that several mutations detected in clinical isolates of these two pathogenic mycobacteria can confer rifampin resistance, but they also suggested that some mutations detected in M. leprae isolates or rifampin-resistant M. tuberculosis isolates are not involved in rifampin resistance.